PENGARUH MODEL PEMBELAJARAN KOOPERATIF STUDENT TEAMS ACHIEVEMENT DIVISIONS DAN CARD SORT UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 1 BANGOREJO BANYUWANGI - Arifin, Zaenal; Priawasana, Endra; Kustiyowati, Kustiyowati (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2023)
The purpose of this study was to determine the effect of the Student Teams Achievement Divisions cooperative learning model and the Sort Card Method on mathematics learning outcomes. This research is included in the causal quantitative type research, namely a study that seeks the influence of certain (independent) variables on other (bound) variables. The research object used a purposive sampling area, namely class VIII students of SMPN 1 Bangorejo Banyuwangi, academic year 2022/2023. The results of the study found that there was an effect of applying the cooperative learning model of the Student Team Achievement Division and Sort Cards simultaneously on improving the mathematics learning outcomes of class VIII students of SMPN 1 Bangorejo Banyuwangi.